Stopping boats, saving lives, securing subjects: Humanitarian borders in Europe and Australia - Little, Adrian; Vaughan-Williams, Nick (European journal of international relations, 2017)
In April 2015, former Australian Prime Minister Tony Abbott called on European leaders to respond to the migration and refugee crisis in the Mediterranean by ‘stopping the boats’ in order to prevent further deaths. This suggestion resonated with the European Union Commission’s newly articulated commitment to both enhancing border security and saving lives. This article charts the increasing entanglement of securitisation and humanitarianism in the context of transnational border control and migration management. The analysis traces the global phenomenon of humanitarian border security alongside a series of spatial dislocations and temporal deferrals of ‘the border’ in both European and Australian contexts. While discourses of humanitarian borders operate according to a purportedly universal and therefore borderless logic of ‘saving lives’, the subjectivity of the ‘irregular’ migrant in need of rescue is one that is produced as spatially and temporally exceptional — the imperative is always to act in the here and the now — and therefore knowable, governable and ‘bordered’.